53‐3: Distinguished Paper: IGZO‐TFT Technology for Large‐screen 8K Display. Issue 1 (30th May 2018) - Hara, Yoshihito; Kikuchi, Tetsuo; Kitagawa, Hideki; Morinaga, Junichi; Ohgami, Hiroyuki; Imai, Hajime; Daitoh, Tohru; Matsuo, Takuya
Abstract : We succeeded in G8 factory for mass production of IGZO‐TFT for the first time in the world. The initial TFT process was an ES type TFT, but now we are mass producing CE type TFTs. And, its application range is smartphones, tablets, PCs, monitors, TV and so on. In particular, due to recent demands for high resolution and narrow frame, our IGZO display has been advanced in technology development with GIP (Gate driver In Panel). In this paper, we report development combining low resistance technology and the latest IGZO‐TFT for large‐screen 8K display.